Smart Toolkit for Evaluating Information Projects, Products and Services: Second Edition: Prelims - Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture; Royal Tropical Institute (Technical Centre for Agricultural and Rural Cooperation, 2009)
In 2001, a group of information practitioners from various development agencies, led by CTA, KIT and IICD, began working together to produce a manual that would support self-evaluation by information practitioners. At their first meeting the word ‘smart’ was chosen to emphasise ‘best practice’ and as an oblique reference to the SMART indicators (specific, measurable, achievable, realistic, time-bound) common in evaluation literature.